Accountability in Infaq Fund Management: The Case of Jogokariyan Mosque - Arif, Muh. Nur; Nugraheni, Bernadia Linggar Yekti (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study investigates the concept of accountability and examines the efforts of the mosque management committee in maintaining financial accountability at Jogokariyan Mosque, Yogyakarta, Indonesia. Using an interpretative qualitative approach and Shariah Enterprise Theory (SET) as the theoretical foundation, this study included semi-structured interviews with 15 participants, including the mosques managers (Taqmirs), congregants, local communities and leaders. The findings indicate that the financial management at Jogokariyan Mosque adheres to the zero-balance principle. Accountability is defined by the Taqmirs' actions in promptly allocating and distributing donation funds to the rightful recipients, followed by maintaining honesty and transparency in their public accountability. The Taqmirs uphold accountability by demonstrating trustworthiness, sincerity, honesty, transparency, and a strong commitment to providing the best service to the community. This research offers a theoretical contribution to accountability concept and to how religious organizations should practice accountability in managing funds from their congregants.